Movement raestraints used in nursing homes for senoirs - Sládek, Miloš (Univerzita Pardubice, 2010)
Care services focused on seniors, namely resident services hold an important position in the system of contemporary social services in the Czech Republic. Admission to a Nursing Home is a major life transition for many olderadults, which influences their lives significantly and almost always permanently. Because of inherent danger of misuse associated with movement restraints together with possible infringement of fundamental human rights and freedoms, there must be strict rules regulating their using. Present regulations are stipulated pursuant to Social Services Act No. 108/2006 as subsequently amended. However the law gives only a general specification, often leading care service providers to very difficult situations. Therefore, a highly important thing is how care service providers observe their obligation – to setup conditions for using physical restraints by internal regulations in individual nursing homes for seniors where it is adequate.
Keywords: nursing homes for seniors; using movement restraints; social services act; reporting use of movement restraints; internal regulations